THE EFFECT OF ORGANIZATIONAL STRUCTURE AND TEAMS PROCESSES TOWARD DECISION MAKING AT ELEMENTARY SCHOOL IN TERNATE MUNICIPALITY - Lukman Tamhir (International Journal of Education, Information Technology, and Others, 2018)
The objective of this study was to know the effect of organizational structure and teams processes toward decision making of elementary school principals in Ternate Municipality. This study consisted of two exogenous variable, they are organizational structure and endogenous variable is decision making of elementary schools principals. The population of this study was all of the elementary school principals in Ternate, they were 100 respondents. The sample was taken by applying simple random sampling. The total sample of this study was 80 principals. The result of study showed that, (1) There is a significant direct effect of organizational structure toward decision making.(2) There is a significant direct effect of team processes toward decision making. (3) There is a significant direct effect of organizational structure toward team processes.Based on the result of this study, the researcher suggested to the principals in order to improve the organizational structure and team processes in school organization so they could make decision effectively, and finally the school goal achieved.